2009
DOI: 10.1136/ard.2008.099531
|View full text |Cite
|
Sign up to set email alerts
|

High systemic bone mineral density increases the risk of incident knee OA and joint space narrowing, but not radiographic progression of existing knee OA: the MOST study

Abstract: Objectives Previous studies suggest that high systemic bone mineral density (BMD) is associated with incident knee OA defined by osteophytes, but not with joint space narrowing (JSN), and are inconsistent regarding BMD and progression of existing OA. We tested the association of BMD with incident and progressive tibiofemoral OA in a large, prospective study of men and women ages 50–79 with, or at risk for, knee OA. Methods Baseline and 30-month weight-bearing PA and lateral knee x-rays were scored for K–L gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
85
3
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 56 publications
12
85
3
1
Order By: Relevance
“…17 Although the populations studied have been predominantly female, there is also evidence of a positive association between BMD and incident knee OA in male populations. 19,20 A similar association between higher BMD and incident radiographic hip OA has been reported in postmenopausal women, 21 whereas Sowers et al 16 found no evidence of a longitudinal association with hand OA in a population of pre-and peri-menopausal women.…”
Section: Bmd and Oa: The Epidemiological Evidence For An Associationmentioning
confidence: 78%
See 3 more Smart Citations
“…17 Although the populations studied have been predominantly female, there is also evidence of a positive association between BMD and incident knee OA in male populations. 19,20 A similar association between higher BMD and incident radiographic hip OA has been reported in postmenopausal women, 21 whereas Sowers et al 16 found no evidence of a longitudinal association with hand OA in a population of pre-and peri-menopausal women.…”
Section: Bmd and Oa: The Epidemiological Evidence For An Associationmentioning
confidence: 78%
“…Hart et al 18 also observed a trend towards lower hip BMD in those with progressive knee OA versus non-progressors. In contrast, Nevitt et al 19 failed to find any association between BMD at the femoral neck or whole body and knee OA progression. If an inverse association between BMD and OA progression does hold true, it may provide important insights into the role of bone in the pathogenesis of OA at different stages of the disease.…”
Section: Bmd and Oa: The Epidemiological Evidence For An Associationmentioning
confidence: 86%
See 2 more Smart Citations
“…Again, this study can only show an association between knee OA and the studied variables, does not imply causation, and should therefore be regarded as hypothesis-generating. Studies suggest that OA and osteoporosis are distinct different diseases [9] and an association between OA in the hip, knee, ankle, and feet and a high BMD has also been found [3,4,6,8,13,17,20,23]. It has been speculated that a high BMD may result in a denser and stiffer skeleton with less load absorptive ability, a phenotype that may be involved in the pathogenesis of primary OA [25].…”
Section: Resultsmentioning
confidence: 99%